2017
DOI: 10.1016/j.prro.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy for oropharyngeal squamous cell carcinoma: Executive summary of an ASTRO Evidence-Based Clinical Practice Guideline

Abstract: The successful management of OPSCC requires the collaboration of radiation, medical, and surgical oncologists. When high-level data are absent for clinical decision-making, treatment recommendations should incorporate patient values and preferences to arrive at the optimal therapeutic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
62
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 28 publications
(34 reference statements)
1
62
2
Order By: Relevance
“…Cancer January 1, 2020 There was a strong statistical effect noted based on tests of interaction between lymph node status and concomitant chemotherapy's association with survival (P for interaction, .001), even after considering multiple hypothesis testing. Although patients with T1-T2N0 disease accounted for only 10% of the current study cohort, the lack of benefit from chemotherapy in these patients noted herein is consistent with the findings of the MACH-NC collaborative group meta-analysis 20 and current treatment guidelines, 21 in which there is little debate that RT alone is the standard of care. These results suggest that the AJCC 7E staging system still is useful for guiding decisions regarding multimodality therapy, similar to historical precedent, even in the era of improved outcomes and HPV-driven disease.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Cancer January 1, 2020 There was a strong statistical effect noted based on tests of interaction between lymph node status and concomitant chemotherapy's association with survival (P for interaction, .001), even after considering multiple hypothesis testing. Although patients with T1-T2N0 disease accounted for only 10% of the current study cohort, the lack of benefit from chemotherapy in these patients noted herein is consistent with the findings of the MACH-NC collaborative group meta-analysis 20 and current treatment guidelines, 21 in which there is little debate that RT alone is the standard of care. These results suggest that the AJCC 7E staging system still is useful for guiding decisions regarding multimodality therapy, similar to historical precedent, even in the era of improved outcomes and HPV-driven disease.…”
Section: Discussionsupporting
confidence: 85%
“…Remarkably, to the best of our knowledge there are almost no comparative effectiveness data in the literature for these patients. In one of the few studies addressing this subgroup, we previously demonstrated that concomitant chemotherapy was associated with improved survival in patients with AJCC 7E cT1‐T2N1 cancers of the oropharynx, larynx, and hypopharynx . However, a limitation of this study was a lack of information regarding HPV status.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The 2016 ACR Appropriateness Criteria has not readdressed this question. The American Society for Radiation Oncology consensus guideline published in 2017 recommended unilateral RT for patients with well‐lateralized (confined to the tonsillar fossa) T1 to T2 tonsillar cancer and N0 to N1 classified disease . It also recommended unilateral RT for patients with lateralized (<1 cm of soft palate extension but without involvement of the base of the tongue) T1 to T2, N0 to N2a tonsillar cancer without clinical or radiographic evidence of ECE.…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of patients who were performed surgery in our series was too limited to draw any conclusion and the question deserves further large comparative studies. As to the role of induction chemotherapy in HPV‐related OPSCC, the recently published evidence‐based clinical practice guidelines of the American Society for Radiation Oncology states that induction should not be routinely delivered to patients with OPSCC, regardless of the HPV status . In patients with HPV‐related OPSCC, 2 phase II trials have recently demonstrated the possibility of treatment de‐escalation with reduced radiation doses and decreased toxicities in responders .…”
Section: Discussionmentioning
confidence: 99%